Estimates of parameters between direct and maternal genetic effects for weaning weight and genetic effects for carcass traits in crossbred cattle - Splan, R.K.; Cundiff, L.V.; Van Vleck, L.D.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Estimates of heritabilities and genetic correlations were obtained from weaning weight records of 23,681 crossbred steers and heifers, and carcass data of 4,094 crossbred steers using REML applied to animal models. Direct and maternal heritabilities for weaning weight were 0.14 and 0.19, respectively. The genetic correlation between direct and maternal weaning weight was negative (-0.18). Heritabilities for carcass traits of steers were moderate to large (0.34 to 0.60). Genetic correlations between direct genetic effects for weaning weight and carcass traits were small, except with hot carcass weight (0.70), ribeye area (0.29) and adjusted fat thickness (0.26). Genetic correlations of maternal genetic effects for weaning weight with direct genetic effects for carcass traits were: hot carcass weight (0.61), retail product percentage (-0.33), fat percentage (0.33), ribeye area (0.29), marbling score (0.28), and adjusted fat thickness (0.25). These results indicate that maternal genetic effects for weaning weight may be correlated with genetics for propensity to fatten in steers. Selection for only direct weaning weight would be expected to increase carcass weight and ribeye area and slightly decrease marbling and retail product percentage. Selection for either increased maternal or direct weaning weight would be expected to result in increased carcass weight, ribeye area, and fat thickness, but would not be expected to affect tenderness.
Keywords: Beef; Genetic effects; Weaning weight; Carcass traits; Crossbred cattle